The impact of elevated dietary inflammatory potential on sarcopenic obesity: evidence from two observational studies - Xi Luo; Weiwei Jin; Shengcheng Mao (Frontiers in Nutrition)
Background and objectiveChronic low-grade inflammation plays a critical role in the onset and progression of both sarcopenia and obesity. Diet, as a well-known modifiable factor of low-grade inflammation, significantly impacts adverse health conditions, including obesity and sarcopenia. This study aims to explore the association between dietary inflammatory potential and sarcopenic obesity (SO).MethodsA total of 4,470 subjects from two National Health and Nutrition Examination Survey (NHANES) cycles (2015–2016 and 2017–2018) and 276 subjects enrolled at Tongde Hospital of Zhejiang Province between January 2024 and February 2025 were enrolled in the present study. Logistic regression was used to investigate the association between the dietary inflammatory index (DII) and SO. Moreover, the mediating effect of C-reactive protein-albumin-lymphocyte (CALLY) and neutrophil-percentage-to-albumin ratio (NPAR) was evaluated to investigate the association between DII and SO in the NHANES cohort.ResultsIn the NHANES cohort, logistic regression demonstrated a positive association between the DII score and SO (adjusted odds ratio (OR) continuous = 1.19, 95% CI = 1.08, 1.32, p = 0.012; adjusted OR tertile3vs1 = 1.93, 95% CI = 1.28, 2.92, p for trend = 0.015). In the Chinese population cohort, a positive association also existed between DII and SO (adjusted OR continuous = 1.59, 95% CI = 1.30, 1.94, p < 0.001; adjusted OR tertile3vs1 = 6.10, 95% CI = 2.72, 13.68, p for trend <0.001). Using the NHANES data, the mediation analysis indicated that CALLY mediated 39.49% of the association between DII and SO, while NPAR mediated 7.35%.ConclusionAn elevated DII score is positively associated with the risk of SO in adults. The association appeared to be partially mediated through inflammatory/nutritional pathways, suggesting that the DII score may serve as a valuable indicator for the identification of individuals at risk of SO.